HIV/AIDS oxidative stress and dietary antioxidants - Preedy, Victor R.; Watson, Ronald R. (Elsevier/Academic Press, 2018)
HIV/AIDS: Oxidative Stress and Dietary Antioxidants provides comprehensive coverage of oxidative stress in HIV/AIDS, focusing on both the pathological process around molecular and cellular metabolism and the complications that can arise due to nutritional imbalance. It provides a pathway for researchers and clinicians to gain an in-depth understanding of the role of oxidative stress, bridging the transdisciplinary divide between virologists, immunologists, physicians, clinical workers, food scientists and nutritionists to advance medical sciences and enable preventative treatment strategies. Very often oxidative stress is a feature of HIV/AIDs or of the treatment of HIV/AIDs. While immunologists, physicians and clinical workers understand the processes in HIV/AIDs, they may be less conversant in the science of nutrition and dietetics. Similarly, nutritionists and dietitians may be less conversant with the detailed clinical background and science of HIV/AIDs.--Provided by publisher.